2021
DOI: 10.1186/s12872-021-01979-7
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between small dense low density lipoprotein and cardiovascular events in patients with acute coronary syndrome undergoing percutaneous coronary intervention

Abstract: Background Residual risk remained significant despite effective low density lipoprotein cholesterol (LDL-C) lowering treatment. Small dense low density lipoprotein cholesterol (sdLDL-C) as part of LDL-C has been found to be predictor of coronary heart disease (CHD) and cardiovascular (CV) events in patients with stable CHD independently of LDL-C. However, to date, few studies have explored the role of sdLDL-C in patients with acute coronary syndromes (ACS) undergoing percutaneous coronary inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 42 publications
0
8
0
Order By: Relevance
“…One year later, the same group reported that sdLDL, HDL-TG and large concentrations of LDL particles were the most powerful predictors of CVD risk ( 8 ). Likewise, in patients with acute coronary syndrome (ACS) who underwent percutaneous coronary intervention (PCI) those with elevated levels of sdLDL have higher risk of CV events compared to those without elevated sdLDL levels ( 9 ).…”
Section: Residual Risk Factorsmentioning
confidence: 99%
“…One year later, the same group reported that sdLDL, HDL-TG and large concentrations of LDL particles were the most powerful predictors of CVD risk ( 8 ). Likewise, in patients with acute coronary syndrome (ACS) who underwent percutaneous coronary intervention (PCI) those with elevated levels of sdLDL have higher risk of CV events compared to those without elevated sdLDL levels ( 9 ).…”
Section: Residual Risk Factorsmentioning
confidence: 99%
“…Few studies investigated the prognostic impact of small dense LDL cholesterol among those with acute coronary syndrome, as examined in this study. In a study conducted by Zhang and colleagues, patients with elevated small dense LDL-cholesterol levels on admission had a higher risk of cardiovascular events in those with acute coronary syndrome receiving percutaneous coronary intervention [ 14 ]. We did not assess small dense LDL-cholesterol levels on admission as the trend in their levels should be determined after initiation of lipid-lowering agents that can also affect small dense LDL-cholesterol levels [ 16 ], most of which are initiated during index hospitalization.…”
Section: Discussionmentioning
confidence: 99%
“…The data on incident risk of small dense LDL cholesterol has primarily been reported among cohorts of patients with stable coronary artery disease [ 5 , 7 , 8 , 9 , 10 , 11 , 12 ], whereas the prognostic impact of small dense LDL-cholesterol levels among those with acute coronary syndrome remains uncertain [ 13 , 14 ]. More data on strategies to enhance secondary prevention of cardiovascular events among those with acute coronary syndrome are needed to prevent downstream events and further improve clinical outcomes following acute coronary syndrome.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Sekimoto and colleagues demonstrated that a small dense LDL-cholesterol > 20.9 mg/dL was associated with higher incidence of adverse events following acute coronary syndrome [ 11 ]. Another recent study also demonstrated that the elevated small dense LDL-cholesterol was a risk factor of future cardiovascular events following acute coronary syndrome [ 14 ]. Given our findings ( Figure 2 A), a cutoff of triglyceride 200 mg/dL, which is a cutoff currently recommended by the guidelines [ 10 ], might not be sufficient as a marker for accurate risk prediction in secondary prevention.…”
Section: Discussionmentioning
confidence: 99%